Quantum steering transfer within quantum network - Xiao-Gang Fan; Jiaojiao Chen; Wei Xiong; Dong Wang; Liu Ye (New Journal of Physics)
Quantum steering is the ability that one system affects another one without delay by performing local measurements, which has garnered significant attention in the field of quantum information science. Here, we propose a linear network to realize tunable quantum steering with adjustable measurements. We show that forward steering of the first entangled source can be perfectly transferred to the state of two endpoints, regardless of measurements in the quantum network. However, for the backward steering between two endpoints, it displays a four-leaf clovers with rich symmetries with measurement parameters $\left\{{{θ _j}} \right\}_{j = 1}^{N - 1}$ and is dependent on the parameters $\left\{{{β _j}} \right\}_{j = 2}^N$ of the input state. By tuning the measurements far away from or close to the optimal values, one-way or two-way steering can be controllably realized. In addition, the error between the actual and optimal measurements is also taken into account in our proposal. The result indicates that a smaller error is beneficial for predicting two-way steering involving multiple measurements. Our proposal offers a promising way to realize the quantum steering transfer within linear networks.